PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK-ANAK DI DESA RIDOGALIH MELALUI PENERAPAN OLAHRAGA TRADISIONAL LOMPAT KARET - Basri, Hasan; Fitria, Dwi Zahra Salsabila; Widyowati, Dian Desty; Putrianika, Puput (Universitas Islam 45 Bekasi, 2024)
Gross motor skills are related to the use of large muscles. To avoid delays in gross motor development in children, it is necessary to develop gross motor skills early on. One of the reasons children's gross motor skills do not develop is because there are no activities in the classroom or school that stimulate children's gross motor development. Childhood is a period of play, therefore, the implementation of the service applies socialization and mentoring methods in encouraging the development of all children, one of which is the traditional game of jumping rope rubber to develop gross motor skills in children. This community service aims to determine the improvement of children's gross motor skills in Ridogalih. The results of the implementation of this community service have a positive impact, namely increasing understanding related to the procedures for implementation and getting to know the traditional sport of rubber jumping more deeply and some children have increased agility and body balance and coordinated their eyes with their hands and feet.